Aprendizagens e formação para o desenvolvimento territorial: o caso do Conectadel no Oeste do Paraná - Kodama, Afonso Kimura (2016)
This study analyzed the graduates of the courses offered by the Regional Training Program for Local Economic Development with Social Inclusion in the Western region of Parana state (ConectaDEL-Brasil program). It was sought to identify how the graduates put into practice the knowledge which is assimilated during the courses and how that knowledge promotes territorial development. In order to reach the proposed objective, the exploratory and descriptive method was used to better understand the processes of formation of local actors and the implications in the territory. As a data collection instrument, structured questionnaires were handed to the graduates of the courses, interviews were conducted with the coordination of the ConectaDEL-Brasil Program and documents related to the execution of the Program were consulted. Data analysis was based on the territorial development approach and the pedagogical approach to territorial development. The results showed that the training processes helped the local actors assimilate the knowledge and strategies necessary to develop actions which promote the development of the territories in which they operate. The main practices of the graduates are the transfer of knowledge to their own network of actors, active participation in the creation of development councils, the articulation of partnerships for the implementation of projects of interest in the territory, the most effective action in the territorial governances which are established in the West and Southwest regions of Parana state and the elaboration fundraising projects. Moreover, it was found that the activities of the ConectaDEL-Brasil Program allowed the participants to establish new contacts and joint work in territorial development projects. On the other hand, the results exposed the lack of planning of the ConectaDEL-Brasil Program in carrying out activities or follow-up of the graduates so that they continue practicing actions that develop the territory.